The Influence of Economic Literacyon Consumption Behaviour Mediated by Local Cultural Values and Promotion - Septiana, Aldila (Dinamika Pendidikan, 2015)
This research aims to know the influence of economics literacy on the students’ consumption behavior through local cultural values and promotions. The mediation used is based on the theories, the empirical studies and the previous studies.Quantitative approach was used in this study. The population was the Pamekasan Senior High Schools students (Class XI IPS, academic year 2012/2013). Proportional random sampling was conducted to take the samples in the population. The data was collected by using the questionnaire and test. Path analysis was used to analyze the data.The findings showe that the economic literacy level influences directly and significantly on the local cultural values, while affected negatively significant on the promotion. Also the economic literacy level influences directly and negatively significant on the consumption behavior. Contrary, the local cultural values influence directly, positively and significantly on the consumption behavior similar to the promotion. Moreover, the economic literacy level influences indirectly and significantly on the consumption behavior through the local cultural values. Similar to the local cultural values, the promotion aspect had the same influence direction. Therefore, this research provided evidence that the economic literacy affected consumption behaviour which are moderated through the value of local culture and promotion aspects